Heat transfers in polymer composite materials : forming processes - Boyard, Nicolas (Mechanical engineering and solid mechanics series., 2016)
This book addresses general information, good practices and examples about thermo-physical properties, thermo-kinetic and thermo-mechanical couplings, instrumentation in thermal science, thermal optimization and infrared radiation.